2012
DOI: 10.1111/j.1463-1318.2012.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary anastomosis vs nonrestorative resection for perforated diverticulitis with peritonitis: a prematurely terminated randomized controlled trial

Abstract: No conclusions may be drawn on preference of one treatment over another from this RCT because it was prematurely terminated following accrual of 15% of its sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(167 citation statements)
references
References 25 publications
2
162
0
3
Order By: Relevance
“…Even if both techniques have shown similar results in terms of efficacy, when considering feculent peritonitis the number of accrued patients is still inadequate to challenge the established use of non-restorative surgery [163,164].…”
Section: What Are the Treatment Options For Feculent Peritonitis?mentioning
confidence: 99%
See 2 more Smart Citations
“…Even if both techniques have shown similar results in terms of efficacy, when considering feculent peritonitis the number of accrued patients is still inadequate to challenge the established use of non-restorative surgery [163,164].…”
Section: What Are the Treatment Options For Feculent Peritonitis?mentioning
confidence: 99%
“…Two prematurely interrupted RCTs [163,164] and several studies with weaker methodology [165,166] have demonstrated similar mortality and morbidity after resection with primary anastomosis and non-restorative procedures: it seems highly unlikely that an exhaustive RCT will be performed [167].…”
Section: What Are the Treatment Options For Purulent Peritonitis?mentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce this bias, introduced by performing PA in more favorable subjects, prospective randomized studies were soon designed and conducted. As stated by the authors, from the prematurely terminated trial by Binda et al [75], no conclusions could be drawn on treatment preference, although they included a total of 90 patients (15% of calculated sample size) of which 15 patients (16.7%) had Hinchey IV. Furthermore, Oberkofler et al [76] published results favoring PA with diverting ileostomy over HP in a total of 62 patients (30 HP vs. 32 PA).…”
Section: Operative Treatmentmentioning
confidence: 95%
“…A further 52 patients presenting during the study period were not assessed for eligibility for inclusion in the trial because the surgeons involved were not willing to enroll the patient, thus introducing the possibility of selection bias. An earlier attempt at a randomized trial also had to be stopped prematurely because of poor recruitment, highlighting the difficulties of performing a randomized trial on an emergency procedure for a potentially life-threatening condition [44].…”
Section: Primary Anastomosis Versus Hartmann's Proceduresmentioning
confidence: 99%